Eficacitatea condiţionărilor pe bază de norfloxacină – Mic ghid - Alin S Deteșan; Romeo Teodor Cristina (Medicamentul Veterinar)
Quinolones have been developed since the 1970s, the first synthesized representative being oxolinic acid. Initially, the components of the group showed significant bactericidal activity only against Gram-negative organisms, their use being limited to enteric and urinary infections. From the variety of formulations available to the poultry practitioner, the quinolone chemotherapeutic conditioning groups are increasingly making their way into the optional palette, due to their undeniable advantages. Later, research paved the way for the second generation of quinolones, namely the fluoroquinolones. The first part of this study reveals bibliographic data useful for those interested in: the mode and mechanism of action of quinolones, the quinolone groups on the market, administration, adverse reactions and precautions, etc. The seccond part presents the clinical testing of an a.u.v. product, an anti-infective powder, based on norfloxacin nicotinate in broiler chickens in poultry units in Caraș Severin County. The research proposes two main objectives: the evaluation of the therapeutic effect in broiler chickens in diseases caused by Gram-positive and Gram-negative germs, sensitive to norfloxacin, and a safety study with the estimation of tolerance and effects following the administration of doses increased by two, three and five times compared to the therapeutic dose.